Optimal load dispatch of multi-source looped district cooling systems based on energy and hydraulic performances. (1st July 2023) - Gao, Cheng; Wang, Dan; Sun, Yuying; Wang, Wei; Zhang, Xiuyu
Abstract: Multi-source looped district cooling (MLDC) systems exhibit promising application potential owing to their ability to utilize various renewable energy resources. The load dispatch for multiple sources is considered a critical factor during operation owing to its effects on the energy and hydraulic performance. However, few studies have investigated the behavior of energy and hydraulic performance under different load dispatch ratios ( LDR s). In addition, straightforward methods for determining the optimal load dispatch of MLDC systems have not been introduced. This study investigated the relationship between the load dispatch and operating performance and proposed a fundamental method to achieve optimal load dispatch for MLDC systems and overcome the existing challenges. A double-source looped district cooling system was selected as the case study, and its Modelica model was developed. Subsequently, we investigated the relationship between the LDR s and operating performance, and verified the existence of an optimal LDR ( LDR opt ), which achieves the best hydraulic performance and lowest energy consumption. Finally, a dataset constructed using a hybrid optimization algorithm was employed to develop a multi-variable data-driven model for predicting LDR opt under various load conditions. This study provides a valuable framework and recommendations for further investigation of the optimal control of MLDC systems. Highlights: The Modelica model of an MLDC system in Beijing was developed and validated. The hydraulic and energy performances under different load dispatch ratios was investigated. The existence of the LDR opt for the MLDC system was verified. A multi-variable linear prediction model of LDR opt was developed.